2001
DOI: 10.4049/jimmunol.166.4.2643
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of Calcium Fluxes and Calmodulin Block Activation of the p21-Activated Protein Kinases in Neutrophils

Abstract: Neutrophils stimulated with fMLP or a variety of other chemoattractants that bind to serpentine receptors coupled to heterotrimeric G proteins exhibit rapid activation of two p21-activated protein kinases (Paks) with molecular masses of ∼63 and 69 kDa (γ- and α-Pak). Previous studies have shown that products of phosphatidylinositol 3-kinase and tyrosine kinases are required for the activation of Paks. We now report that a variety of structurally distinct compounds which interrupt different stages in calcium/ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 54 publications
3
37
1
Order By: Relevance
“…We provide evidence that a selective p38 kinase inhibitor, SB202190, and DNM-p38 had no effect on p90 RSK Ser 381 phosphorylation and its kinase activity induced by UVA. Although the studies of Lian et al (46) and Horstmann et al (67) suggested that the p38 kinase inhibitor-sensitive pathway was involved in activation of S6 kinases, our data suggest that UVA-induced Ser 381 phosphorylation may not be dependent on p38 kinase. The discrepancy may be related to cell type and the kind of stimuli.…”
Section: Discussioncontrasting
confidence: 83%
“…We provide evidence that a selective p38 kinase inhibitor, SB202190, and DNM-p38 had no effect on p90 RSK Ser 381 phosphorylation and its kinase activity induced by UVA. Although the studies of Lian et al (46) and Horstmann et al (67) suggested that the p38 kinase inhibitor-sensitive pathway was involved in activation of S6 kinases, our data suggest that UVA-induced Ser 381 phosphorylation may not be dependent on p38 kinase. The discrepancy may be related to cell type and the kind of stimuli.…”
Section: Discussioncontrasting
confidence: 83%
“…Increased intracellular calcium is a ubiquitous second messenger of downstream signaling. Heterotrimeric G proteins can activate Ras via phosphatidylinositol-specific phospholipase C and Ca 2ϩ /calmodulin complex (61)(62)(63). Inhibition of intracellular calcium channels, Ca 2ϩ /calmodulin complex, and Ca 2ϩ /calmodulin kinase blocked PAK activation in fMLP-stimulated neutrophils (62).…”
Section: Discussionmentioning
confidence: 99%
“…31). Preparation of phosphorylated GST-Pak 3 and in vitro dephosphorylation of this protein catalyzed by PP 1, PP 2A, PP 2B, and PP 2C.…”
Section: Methodsmentioning
confidence: 99%